Physicochemical and sensory characteristics of iron rich macarons based on red rice and moringa leaf flour - Wahyu Utami, Nurul; Ratnaningsih, Nani (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2026)
ABSTRAK Latar Belakang: Remaja putri di Indonesia beresiko tinggi mengalami anemia akibat kekurangan zat besi dengan prevalensi 32,0%. Konsumsi pangan sumber zat besi dapat mencegah anemia, misalnya beras merah dan daun kelor. Namun pengembangan kukis dari beras merah dan daun kelor masih terbatas, termasuk pada produk macaron yang terbuat dari tepung almond dan putih telur. Tujuan: Penelitian ini bertujuan untuk menemukan formula, menguji kadar proksimat dan zat besi, serta tingkat kesukaan remaja terhadap macaron substitusi tepung beras merah dan tepung kelor. Metode: Penelitian RnD untuk menguji kadar proksimat dan kadar besi. Macaron yang diuji adalah F0 (0% tepung beras merah, 0% tepung kelor), F1 (60% tepung beras merah, 0% tepung kelor), dan F2 (60% tepung beras merah, 3% tepung kelor). Analisis statistik menggunakan uji One-Way Anova dan uji lanjutan Tukey HSD. Hasil: Macaron dengan substitusi 60% tepung beras merah dan 3% tepung kelor memiliki kandungan gizi per 100 g berupa 3.28±0.11 g air, 1.58±0.28 g abu, 19.56±0.00 g lemak, 18.21±0.54 g protein, 70.61±0.71 g karbohidrat, dan 11.49±0.05 mg zat besi. Kadar zat besi macaron per porsi (45 gram) memenuhi 34.47% kebutuhan zat besi remaja sehingga dikategorikan sebagai pangan tinggi zat besi. Hasil uji hedonik menunjukkan macaron substitusi 60% tepung beras merah dan 3% tepung kelor disukai oleh remaja dan berbeda nyata dengan produk acuan. Kesimpulan: Macaron substitusi 60% tepung beras merah dan 3% tepung kelor dikategorikan sebagai kukis tinggi zat besi karena dapat memenuhi 34.47% angka kecukupan zat besi remaja sehingga berpotensi sebagai pangan fungsional untuk mencegah anemia pada remaja. ABSTRACT Background: Adolescent girls are at high risk of anemia caused by iron deficiency. Anemia is a condition characterized by a deficiency of hemoglobin or red blood cells that falls below normal levels. Consumption of iron-rich foods can prevent anemia. Moringa leaves are a superfood with an iron content of 28.2 milligrams. Macarons are cookies made from almond flour and egg whites. Substituting moringa flour in macarons is expected to increase their iron content. Objectives: This study aims to analyze the proximate composition, iron content, and acceptability of macarons substituted with brown rice flour and moringa flour. Methods: R&D research was conducted to test the proximate composition and iron content. The macarons tested were F0 (0% red rice flour, 0% moringa flour), F1 (60% red rice flour, 0% moringa flour), and F2 (60% red rice flour, 3% moringa flour). Statistical analysis was performed using One-Way ANOVA and Tukey HSD post-hoc tests. Results: The nutritional composition of macarons with 60% red rice flour and 3% moringa flour substituted per 100 g consists of 3,28±0.11 g water, 1,58±0.28 g ash, 19,56±0.00 g fat, 18,21±0.54 g protein, 70,61±0.71 g carbohydrates, and 11.49±0.05 mg iron. The iron content of macarons per serving (45 grams) can meet 34,47% of the iron requirement for adolescents, thereby classifying these macarons as iron-rich food. The hedonic test results showed that macarons with a substitution of 60% red rice flour and 3% moringa flour were preferred by adolescents and significantly different from the reference product. Conclusions: Macarons with a substitution of 60% red rice flour and 3% moringa flour are categorized as iron-rich cookies because they can meet 34,47% of the iron requirement for adolescents, making them a potential functional food for preventing anemia in adolescents.   KEYWORD: macaron; red rice flour; moringa flour; iron; adolescents